2021
DOI: 10.1016/j.jceh.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Predictors of Mortality in Patients With Drug-Induced Liver Injury at a Tertiary Hospital in South India: A Single-Centre Experience

Abstract: Introduction: Drug-induced liver injury (DILI) is an important cause of acute liver failure with significant morbidity and mortality. The outcome of DILI varies widely according to the drug implicated and the type of liver injury. Owing to the heterogeneous nature of liver injury, knowledge on clinical course and prognosis of DILI is limited. We had undertaken this study to determine the clinical characteristics, outcomes, and predictors of mortality in patients with DILI. Materials and methods: This prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…DILI is the main cause of acute liver failure ( Sunil Kumar et al, 2021 ), and it is very important to predict and prevent DILI. We collected the information of drug properties and DILI endpoints of FDA-approved drugs and studied the risk factors toward DILI and the associations between KIs and DILI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DILI is the main cause of acute liver failure ( Sunil Kumar et al, 2021 ), and it is very important to predict and prevent DILI. We collected the information of drug properties and DILI endpoints of FDA-approved drugs and studied the risk factors toward DILI and the associations between KIs and DILI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the DILI occurrence was associated with the drug types ( Sunil Kumar et al, 2021 ). Anti-tumor drugs, heparin, antibacterial drugs, and anti-tuberculosis drugs are the most common drug categories that cause DILI in clinical practice ( Meier et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs and drug metabolites are capable of damaging the liver, resulting in a spectrum of symptoms ranging from mild to acute liver failure. The most common drugs inducing liver injury are antimicrobials [ 72 , 73 , 74 ]. Despite the rare incidence and uncommon cause of acute liver failure, DILI poses a threat to morbidity and mortality.…”
Section: Drug-induced Liver Injury (Dili) In Personalized Medicinementioning
confidence: 99%